Phytochemical Investigation and Hypoglycaemic Activity of Tribulus terrestris - Manogaran, S.; Sulochana, N. (Asian Journal of Chemistry, 2016)
The flowers of Tribulus terrestris were analyzed phytochemically and the compound was isolated from extract. The compound was characterized by chemical and spectral methods and found to be quercetin 3-O-rhamnoside.